A nonenzymatic uric acid sensor based on electrophoretically deposited Graphene/ITO electrode. (26th October 2022) - Toan, Tran Quoc; Dung, Nguyen Quoc; Truong, Mai Xuan; Van Hao, Pham; Hien, Trinh Ngoc; Van Dang, Nguyen; Anh, Le Phuoc; Hoa, Nguyen Xuan; Thuy, Pham Thi; Van Thanh, Dang
Abstract: A nonenzymatic uric acid sensor is proposed based on an electrophoretically deposited Graphene/ITO electrode (EDG). The morphology and structure of the EDGs were characterized by scanning electron microscopy (SEM) and Raman spectroscopy. As a result, the EDGs electrode was successfully fabricated with a well‐adhered graphene film on the ITO substrate surface. The electrochemical properties of the EDG for uric acid were investigated in PBS buffer pH 7.4, using cyclic voltammetry (CV) studies. Quantification of uric acid using both cyclic scanning and differential addition polarization methods. As a result, the uric acid sensor has a linear range from 1 to 100 μM, sensitivity 318.4 (μAcm 2 mM ‐1 ) from CV measurements. Moreover, by the differential pulse voltammetry (DPV), the sensor has a linear range from 1 to 50 μM, a sensitivity of 1242.7 (μAcm 2 mM ‐1 ), and the detection limit (LOD) of 0.6 μM (S/N = 3). The oxidation peak potential separation of uric acid, ascorbic, and dopamine at the EDG electrode showed that the uric sensor could eliminate interferences (ascorbic acid, dopamine) and be used to simultaneously determine uric acid, ascorbic acid, and dopamine. Abstract :